Projecting the benefits of golden rice in the Philippines - Roukayatou Zimmermann; Matin Qaim (University of Bonn, Center for Development Research (ZEF), 2002)
Golden Rice has been genetically engineered to produce beta-carotene in the endosperm of the grain. It could improve the vitamin A status of deficient food consumers, especially women and children in the developing world. This paper analyses the potential impacts in a Philippine context. Since the technology is still at the stage of R&D, benefits are simulated within a scenario approach. The health effects are quantified using the methodology of disability-adjusted life years (DALYs). Golden Rice will not completely eliminate the problems of vitamin A deficiency, such as blindness or increased mortality rates. So it should be seen as a complement rather than a substitute for alternative interventions. Yet, the technology will reduce related health costs significantly. In monetary terms, annual gains will lie between 23 million and 137 million, depending on the underlying assumptions. A preliminary cost-benefit analysis shows high returns on R&D investments. Micronutrient-enriched crops are an efficient way to reduce deficiency problems among the poor, and related research projects should receive higher political priority.
Keywords: 330; Crop Production/Industries; Research and Development/Tech Change/Emerging Technologies; Agrarbiotechnologie; Reis; Ernährung; Gesundheitskosten; Kosten-Nutzen-Analyse; Philippinen